2020
DOI: 10.1186/s13741-020-00148-2
|View full text |Cite
|
Sign up to set email alerts
|

Why women are not small men: sex-related differences in perioperative cardiopulmonary exercise testing

Abstract: Background: The use of preoperative cardiopulmonary exercise testing (CPET) to evaluate the risk of adverse perioperative outcomes is increasingly prevalent. CPET-derived information enables personalised perioperative care and enhances shared decision-making. Sex-related differences in physical fitness are reported in non-perioperative literature. However, little attention has been paid to sex-related differences in the context of perioperative CPET. Aim: We explored differences in the physical fitness variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Additional support for their approach comes from Elmariah et al 13 who found that women with heart failure had lower VȮ 2peak values than their male counterparts, yet had better 1-year survival outcomes. Thomas et al 14 also found significantly lower VȮ 2peak and AT values in females awaiting major colorectal surgery but also reported no sex differences in mortality or morbidity. Like Rose and colleagues, the respective authors both concluded that the application of universal CRF thresholds was inappropriate and called for sex-specific pre-operative CPET thresholds to be included in future guidelines.…”
Section: Cardiorespiratory Fitness Number Of Paɵents Undergoing Pre-o...mentioning
confidence: 90%
See 1 more Smart Citation
“…Additional support for their approach comes from Elmariah et al 13 who found that women with heart failure had lower VȮ 2peak values than their male counterparts, yet had better 1-year survival outcomes. Thomas et al 14 also found significantly lower VȮ 2peak and AT values in females awaiting major colorectal surgery but also reported no sex differences in mortality or morbidity. Like Rose and colleagues, the respective authors both concluded that the application of universal CRF thresholds was inappropriate and called for sex-specific pre-operative CPET thresholds to be included in future guidelines.…”
Section: Cardiorespiratory Fitness Number Of Paɵents Undergoing Pre-o...mentioning
confidence: 90%
“…The sex‐specific thresholds (dashed lines) represent the reformulated female (V̇O 2peak <11.9 mL kg −1 min −1 and V̇E/V̇CO 2 ‐AT >35) and male (V̇O 2peak 14.9 mL kg −1 min −1 and V̇E/V̇CO 2 ‐AT >33) specific thresholds proposed by Rose et al to normalise and account for the well‐recognised sex‐differences in cardiorespiratory fitness. Panel A based upon data shown by Kaminsky et al, 12 and Panel B adapted from Thomas et al 14 …”
Section: Figurementioning
confidence: 99%
“…Female inclusion rate in peer‐reviewed publications of perioperative CPET is reported at only 31% and may have a bearing on the interpretation of data (Thomas et al., 2020). Surprisingly, despite evidence that CRF is lower in females across the lifespan, given smaller body size, skeletal muscle mass, peak cardiac output and Hb concentration (Jackson et al., 2009; Fleg et al., 2005), sex is not considered during surgical risk stratification.…”
Section: Optimising Risk Quantification and Patient Managementmentioning
confidence: 99%
“…Preoperative CPET is used to identify patients with low CRF which is an established predictor of survival following major intra‐abdominal surgery 5–9 . When comparing the sexes, female patients demonstrate lower preoperative CRF than males 10 . However, to what extent sex differences in CRF influence preoperative risk stratification and corresponding ‘normalization’ approaches to optimize the latter has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] When comparing the sexes, female patients demonstrate lower preoperative CRF than males. 10 However, to what extent sex differences in CRF influence preoperative risk stratification and corresponding 'normalization' approaches to optimize the latter has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%